Push-out tests: connections by adherence in the context of latticed joist slabs - Lisarb Henneh Brasil; Hidelbrando José Farkat Diógenes; Maria Isabel Brito Valente; Lays Raianne Azevedo da Costa (Revista IBRACON de Estruturas e Materiais, 2023)
Abstract Composite structures and precast solutions stand out because they lead to simple, fast erected and economic constructions. In steel-concrete composite construction, shear connectors are used to assure the shear transfer between the steel profile and the concrete slab, enabling the composite action to develop. This paper discusses an innovative technology for connection by adherence, whose resistance is due to friction on various steel-concrete interfaces. The authors consider that this type of shear connection is suitable for composite beams with latticed joists slabs, and the study developed intends to analyze the behavior of the proposed connection, in this application's context, through experimental and numerical approaches. For this purpose, push-out specimens were fabricated and tested in accordance with Eurocode-4 requirements, where the connection behavior is analyzed in terms of its load-slip relation, and the failure modes are identified. Experimental and numerical results allowed to induce that the connector by adherence made with a checkered steel plate is appropriate to be used in composite structures, as it exhibits satisfactory shear resistance and ductility performance. Also, specimens with latticed joist slabs presented average load capacity values with the same magnitude as the average load capacity obtained in models with solid slabs, despite being more prone to cracking. From the parametric study, an increase of 100% in the connector height implied strength increase from 16% to 25%, depending on slab type.